Age and sex-related differences in elastic properties of the gastrocnemius muscle-tendon unit: an observational prospective study - Zhang, Zhijie; Wang, Wenjing; Li, Feng; Guo, Jiayi (Frontiers in Aging, 2024)
IntroductionChanges in the mechanical properties of the gastrocnemius muscle-tendon unit can lead to abnormal biomechanics of lower limbs, which is a risk factor for the development of many diseases. However, fewer studies have explored physiological changes in the gastrocnemius muscle-tendon unit stiffness. This study aimed to investigate the age- and sex-related differences in the gastrocnemius muscle-tendon unit stiffness.MethodsThe study included 20 older women, 20 young women, and 20 older men. Shear wave elastography (SWE) was used to measure the stiffness of the medial gastrocnemius (MG), lateral gastrocnemius (LG), and Achilles tendon (AT) in all subjects in relaxed, neutral, and standing positions.ResultsThe results showed no significant differences in the MG, LG, and AT stiffness between the dominant and non-dominant sides (p > 0.05). The MG, LG, and AT stiffness changed with positions (p < 0.05). The LG stiffness in older women was lower than in older men and young women in any position (p < 0.05). The MG stiffness in older men was greater than that in older women in any position, and age-related changes were found only in the relaxed and standing positions (p < 0.05). The AT stiffness was higher in older men only in the relaxed position (p < 0.05). There was no significant difference in AT stiffness between older and younger women at any position (p > 0.05).DiscussionThese results suggest that the bilateral gastrocnemius muscle-tendon unit stiffnesses were similar regardless of sex, age, and position. The stiffness of the gastrocnemius in women decreased with age. However, the effect of aging on AT stiffness was slight. Men have greater gastrocnemius stiffness in older adults.